The Influence of Motivation, Discipline, and Work Environment on Employee Performance - Elisabeth, Cherly (Golden Ratio of Data in Summary, 2023)
This research aimed to know and analyzed the influence of positive motivation, discipline, and job environment variables on performance by an employee on the Secretariat of General Election Commission East Luwu Regency and to know and analyzed the dominant variable toward performance by an employee on Secretariat of General Election Commission East Luwu Regency. This research used descriptive and quantitative approaches. Total respondents of research namely all employees of the Secretariat of General Election Commission East Luwu Regency amount to 35 respondents. The method of gathering data which used namely observation, interview, questionnaire, and documentation. The result analyzed from the F-test obtained count> F-table, so from the result it can to conclusion that simultaneously the motivation, discipline, and job environment variables influenced the performance of an employee on Secretariat of General Election Commission East Luwu Regency. From the result of the F-test and coefficient, the correlation can know also that the motivation, discipline, and job environment toward performance amount to 65,6% which means 34,4% influenced by another variable which was not observed in this research. The result of research from t-test obtained of t-count from each independent variable> t-table, with this can to conclusion that all the independent variables partially influenced toward performance by the employee on Secretariat of General Election Commission East Luwu Regency. Through the result of the coefficient, a regression can know that the dominant variable which influenced performance namely discipline.